The Center of Neville's Vision: An Elegant Axiology. - Frankenberry, Nancy (American Journal of Theology & Philosophy, 2019)
This essay examines three themes that form the foundation of Neville's philosophical system as formulated in his trilogy Axiology of Thinking, which consists of Reconstruction of Thinking (volume 1), Recovery of the Measure (volume 2) and Normative Cultures (volume 3). Some questions are raised about each theme, as well as about the very meaning of "foundation" as it plays out in Neville's ontology.